EL GÉNERO CAMELOBA ETIDIUS (EPHEMEROPTERA : BAETIDA E) EN LA A RGENTINA - Nieto, Carolina (Instituto de Ecología, A.C., 2003)
The genus Camelobaetidius (Ephemeroptera: Baetidae) in A rgentina. Camelobaetidius ipaye sp. nov., C.apis sp. nov., C. yacutinga sp. nov., and C. huarpe sp. nov., from A rgentina, are described and illustrated from nymphs, and in the last case from female imago. Three species are recorded for the first time from A rgentina: C. tuberosus (Lugo-Ortiz & McCafferty 1999), C. anubis (Traver & Edmunds 1968), C. phaedrus (Traver & Edmunds 1968), and the adults of the last two are described. Keys to separate both adults and nymphs from the A rgentinian species are provided, and species distributions are included.